2021
DOI: 10.3344/kjp.2021.34.2.229
|View full text |Cite
|
Sign up to set email alerts
|

The role of the iliotibial band cross-sectional area as a morphological parameter of the iliotibial band friction syndrome: a retrospective pilot study

Abstract: Background: Iliotibial band friction syndrome (ITBFS) is a common disorder of the lateral knee. Previous research has reported that the iliotibial band (ITB) thickness (ITBT) is correlated with ITBFS, and ITBT has been considered to be a key morphologic parameter of ITBFS. However, the thickness is different from inflammatory hypertrophy. Thus, we made the ITB cross-sectional area (ITBCSA) a new morphological parameter to assess ITBFS. Methods: Forty-three patients with ITBFS group and from 43 normal group who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Park et al (11) average ITBT they measured 1.9±0.4 mm in the normal group and 2.6±0.5 mm in the ITBFS group. They also measured the ITB area in their study and found the mean ITB area was 25.2±6.6 mm2 in the normal group and 38.8±9.1 mm2 in the group with ITBFS.…”
Section: Methodsmentioning
confidence: 92%
“…Park et al (11) average ITBT they measured 1.9±0.4 mm in the normal group and 2.6±0.5 mm in the ITBFS group. They also measured the ITB area in their study and found the mean ITB area was 25.2±6.6 mm2 in the normal group and 38.8±9.1 mm2 in the group with ITBFS.…”
Section: Methodsmentioning
confidence: 92%
“…Therefore, accurate diagnosis of ITBFS is important. Previous studies reported that a higher position of patella (patella alta), lateral epicondyle prominence (increment in lateral epicondyle height), thick ITB, and larger ITB-a were the morphological features associated with ITBFS [ 6 9 ]. However, these are subjectively measured values and there are not many studies on their reliability.…”
Section: Discussionmentioning
confidence: 99%
“…3 ), 4) ITB diameter (ITB-d) was measured in the thickest region at the level of lateral femoral epicondyle on an axial T2-weighted FS image. On the same axial image plane, the ITB area (ITB-a) was also measured by drawing free-hand region of interests (ROIs) at the thickest ITB [ 8 , 9 ] ( Fig. 4 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We would like to congratulate Dr. Park and the team for their recently published article titled “The role of the iliotibial band cross-sectional area as a morphological parameter of the iliotibial band friction syndrome: a retrospective pilot study” [ 1 ]. In the aforementioned study, they examined whether the cross-sectional area of the iliotibial band (ITB) was superior to its thickness for diagnosis of ITB friction syndrome.…”
Section: To the Editormentioning
confidence: 99%